A phenomenological investigation on ethical leadership and workplace engagement from a multi-cultural perspective - Adnan, Nosheen; Bhatti, Omar Khalid; Baykal, Elif (Canadian Institute for Knowledge Development-Child, 2022)
Despite continuous attempts to introduce employee engagement measures, leaders worldwide have been increasingly concerned about diminishing employee engagement levels. The issue of workplace engagement continues to be a source of contention for academics and practitioners alike. There is still a need to comprehend this phenomenon since previous research lacks a thorough understanding of employee work engagement concerning ethical leadership. This qualitative study explores the perceptions of the leaders working in service organizations regarding ethical leadership on employee work engagement in three countries, i.e., Malaysia, Turkey, and Pakistan. The phenomenon of work engagement was explored in this study. The theory of self-determination supports the proposed theoretical framework of the current study. Purposive sampling was applied to select 28 leaders in the service sector. Semi-structured interviews were performed to understand employee engagement better using participant observations, opinions, strategic perspectives, and the employee handbook and recordings of interviews and meetings with service sector leaders. The findings highlighted eight major ethical leadership themes suggested by 28 managers in the interviews. Eight themes of ethical leadership are (1) Role Modeling, (2) Trust, (3 Honesty, (4) Integrity, (5) Justice, (6) Religiosity, (7) Responsibility, (8) Intellectual competence. The present study found that leaders applying different strategies and understanding the importance of employee engagement could improve employee engagement and have a more robust workforce and beneficial organization. (C) CIKD Publishing.
Keywords: Ethical Leadership; Employee Work Engagement; Ethical Practices; Self-Determination Theory; Service Sector